A NEW NON-INVASIVE DEVICE TO MONITOR CORE TEMPERATURE ON EARTH AND IN SPACE - Hanns-Christian Gunga; Andreas Werner; Oliver Opatz; Alexander Stahn; Karl Kirsch; Frank Sattler; Jochim Koch (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Accurate measurement of the core body temperature (cbt) is fundamental to the study of human temperature regulation. As standard sites for the placement of cbt measurement sensors have been used: the rectum, the bladder, the esophagus, the nasopharynx and the acoustic meatus. Nevertheless those measurement sites exhibit limited applicability under field conditions, in rescue operations or during peri- and postoperative long-term core temperature monitoring. There is, indeed, a high demand for a reliable, non-invasive, easy to handle telemetric device. But the ideal non-invasive measurement of core temperature has to meet requirements such as i) a convenient measurement site, ii) no bias through environmental conditions, and iii) a high sensitivity of the sensor regarding time shift and absolute temperature value. Recently, together with the Draegerwerke AG we have developed a new heat flux measurement device (so-called "Double Sensor") as a non-invasive cbt sensor aiming to meet the requirements described above. Four recent studies in humans will be summarized and discussed to show the applicability of this new non-invasive method to monitor core temperature under different environmental and clinical settings on Earth and in space.